Image-based computer modeling assessment of microwave ablation for treatment of adrenal tumors. (31st December 2022) - Sebek, Jan; Cappiello, Grazia; Rahmani, George; Zeinali, Nooshin; Keating, Muireann; Fayemiwo, Michael; Harkin, Jim; McDaid, Liam; Gardiner, Bryan; Sheppard, Declan; Senanayake, Russell; Gurnell, Mark; et al.
Abstract: Purpose: To assess the feasibility of delivering microwave ablation for targeted treatment of aldosterone producing adenomas using image-based computational models. Methods: We curated an anonymized dataset of diagnostic 11 C-metomidate PET/CT images of 14 patients with aldosterone producing adenomas (APA). A semi-automated approach was developed to segment the APA, adrenal gland, and adjacent organs within 2 cm of the APA boundary. The segmented volumes were used to implement patient-specific 3D electromagnetic-bioheat transfer models of microwave ablation with a 2.45 GHz directional microwave ablation applicator. Ablation profiles were quantitatively assessed based on the extent of the APA target encompassed by an ablative thermal dose, while limiting thermal damage to the adjacent normal adrenal tissue and sensitive critical structures. Results: Across the 14 patients, adrenal tumor volumes ranged between 393 mm 3 and 2, 395 mm 3 . On average, 70% of the adrenal tumor volumes received an ablative thermal dose of 240CEM43, while limiting thermal damage to non-target structures, and thermally sparing 83.5–96.4% of normal adrenal gland. Average ablation duration was 293 s (range: 60–600 s). Simulations indicated coverage of the APA with an ablative dose was limited when the axis of the ablation applicator was not well aligned with the major axis of the targeted APA. Conclusions: Image-based computational models demonstrate the potential for delivering microwave ablation to APA targets within the adrenal gland, while limiting thermal damage to surrounding non-target structures.